Intelligent computing theories and technology. 12th International Conference, ICIC 2016, Lanzhou, China, July 28-31, 2013. Proceedings /: 12th International Conference, ICIC 2016, Lanzhou, China, July 28-31, 2013. Proceedings. Part II : (2016) - Unknown
No abstract available